Characterization of the physical properties of electron-beam-irradiated white rice and starch during short-term storage. - Zhihong Du; Jiali Xing; Xiaohu Luo; Li Wang; Lihong Pan; Yulin Li; Ren Wang; Yuntao Liu; Xiaohong Li; Zhengxing Chen (PLoS ONE)
Electron-beam irradiation (EBI) is a cold sterilization technology used in the irradiation processing of food, including rice. Herein, the effects of EBI on the swelling power, color, pasting, and sensory properties of white rice after short-term storage were analyzed. Samples were electron-beam irradiated at 0, 2, 4, 6, or 8 kGy and stored at 25 °C or 37 °C for up to 75 days. Results showed that swelling power and major pasting viscosities (including peak, breakdown, and setback viscosities) at both storage temperatures decreased with increased irradiation dose. Negative correlations were also observed between the major viscosities of pasting properties and irradiation dose at both storage temperatures. During sensory evaluation, extremely low scores for rice hardness, appearance, taste, and overall acceptability were obtained for rice subjected to high EBI dose (>4 kGy). However, rice stored at 37 °C showed lower performance than rice at 25 °C in terms of the abovementioned parameters. By contrast, the sensory properties at irradiation doses between 2 and 4 kGy were better than those of the control group at both storage temperatures. All these findings indicated the potential of low-dose (<4 kGy) EBI as pretreatment for improving the quality of white rice during storage.